2017
DOI: 10.1007/s10043-017-0307-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of CrSe thin film produced via chemical bath deposition

Abstract: are rarely produced. However, CrSe alloy is a very interesting material because of its magnetic properties [1]. The chromium selenide analogue Cr (1 − x) Se (x) is well known as antiferromagnetic [2]. The metallic chromium selenides as Cr 3 Se 4 and Cr 2 Se 3 are antiferromagnets and semiconductors [3][4][5]. Some transition metal chalcogenides are found to be excellent candidates for half-metallic ferromagnets according to literature [6].It is already known that chromium selenide has a monoclinic structure, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These films together with the graphene/CrSe heterostructure showed quantum Hall plateau and quantum oscillations assuring the successful application of CrSe in nano-electronics [11]. CrSe thin films prepared by CBD technique displayed wide variety in the optical and dielectric properties which can be controlled by varying the PH value [12,13]. Unfortunately chromium selenide thin films prepared by this method showed low dielectric constant values [12,13].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These films together with the graphene/CrSe heterostructure showed quantum Hall plateau and quantum oscillations assuring the successful application of CrSe in nano-electronics [11]. CrSe thin films prepared by CBD technique displayed wide variety in the optical and dielectric properties which can be controlled by varying the PH value [12,13]. Unfortunately chromium selenide thin films prepared by this method showed low dielectric constant values [12,13].…”
Section: Introductionmentioning
confidence: 91%
“…CrSe thin films prepared by CBD technique displayed wide variety in the optical and dielectric properties which can be controlled by varying the PH value [12,13]. Unfortunately chromium selenide thin films prepared by this method showed low dielectric constant values [12,13]. This feature makes the use of CrSe in high k optoelectronics hardly possible.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher repeated the measurements by changing the pH value of the chemical bath between 8 and 11 and showed that the optical bandgap of the forbidden energy range is changing with changing pH values. [ 226 ]…”
Section: The Properties Of Rmcsmentioning
confidence: 99%
“…The researcher repeated the measurements by changing the pH value of the chemical bath between 8 and 11 and showed that the optical bandgap of the forbidden energy range is changing with changing pH values. [226] Kocyigit et al fabricated a photodiode by using a Cu 2 WSe 4 interfacial layer and examined the photoelectrical, morphological, and capacitive attitudes. In the performed measurements, they found the ideality factor and barrier height values as 4.84 and 0.82 eV, respectively.…”
Section: Electrical and Optical Properties Of Rmcsmentioning
confidence: 99%
“…Optical properties such as refractive index (1.16 to 1.54), extinction coefficient (5.1 X 10 -4 to 4.9 X 10 -3 ), real dielectric constant (2.36 to 1.36) and band gap (1.7 to 2.3 eV) were investigated under various pH values (pH 10-13). Kariper 67 conclude that increasing the pH from 7 to 10 could increase the film thickness (74.6 to 138.2 nm) because of the presence of hydroxide ions in the media. Further, the researcher explains that transmittance (16.7 to 52.5 %) and reflectance (16.7 to 39.7 %) data did not vary based on film thickness due to either cadmium or selenium was dominant in specific experimental conditions.…”
Section: Chemical Bath Deposited Cadmium Selenide Thin Filmsmentioning
confidence: 99%